Slovak Republic : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper uses the case of the Slovak Republic to investigate how European Union (EU) countries can make optimal use of EU funds to reduce regional disparities. The findings suggest that high-quality government and a more educated population lead to better absorption of EU funds. There is also evidence that absorption increases when spending is more decentralized. Regions with a sufficient level of human capital and adequate institutions are more likely to spend the allocated funds efficiently and to experience growth as a result. With appropriate administrative and governance capacities, fighting corruption should therefore be the priority to speed absorption and allow for higher-quality projects.